High-Risk HPV with Multiple Infections Promotes CYP2E1, Lipoperoxidation and Pro-Inflammatory Cytokines in Semen of Asymptomatic Infertile Men - Elvia Pérez-Soto; María Olivia Medel-Flores; Eduardo Fernández-Martínez; Rigoberto Oros-Pantoja; José Cruz Miranda-Covarrubias; Virginia Sánchez-Monroy (MDPI AG, 2022)
High-risk human papillomavirus (HR-HPV) infection, followed by chronic inflammation and oxidative stress, is a major risk factor of male infertility. In this study, we explored the potential impact of high-risk (HR) HPV genotypes in single infection (SI) and multiple infections (MI) that promote CYP2E1 expression, oxidative damage and pro-inflammatory cytokines, possibly contributing to sperm damage and male infertility. Semen samples from 101 infertile military men were studied. We analyzed seminal parameters, namely, HPV genotyping, cytochrome P450 2E1 (CYP2E1), oxidative stress biomarkers (total antioxidant capacity (TAC), catalase (CAT) and superoxide dismutase (SOD)), lipid peroxidation (LPO), 8-hydroxiguanosine (8-OHdG) and pro-inflammatory cytokines (IFN-γ, IL-1β, IL-4, IL-6 and IL-8). Eighty-one men (80.2%, 81/101) were positive for HPV infection, and MI-HR-HPV was higher than SI-HR-HPV (63% vs. 37%). HPV-52 was the most frequently detected type (18.5%), followed by HPV-33 (11.1%), and the most frequent combination of genotypes detected was HPV-33,52 (11.1%), followed by HPV-18,31 (6.2%). The group with infected samples presented lower normal morphology and antioxidant levels compared to non-infected samples. In concordance, the infected group showed high levels of LPO, IFN-γ, IL-1β, IL-4 and IL-6 and downregulation of CAT and SOD enzymes. Interestingly, changes in motility B, low levels of TAC, overexpression of CYP2E1, LPO and IL-8 levels were higher in MI-HR-HPV than SI-HR-HPV, suggesting that HPV infection promotes a chronic inflammatory process and a toxic and oxidative microenvironment, which increases with MI-HPV infections.